Strategi Kolaboratif Guru BK dengan Guru PAI dalam Membentuk Akhlakul Karimah Siswa - Mira Herdiani; Aep Kusnawan; Hajir Tajiri (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2018)
This study illustrates student’s profile, the collaboration of BK teachers with PAI teachers, collaborative methods and results achieved from the collaboration in shaping students good deeds in Madrasah Tsanawiyah Al-Mukhlisin. The research method used is qualitative descriptive method. Based on the results of the study found collaborative strategies of teachers BK with teachers PAI in Madrasah Tsanawiyah Al-Mukhlisin running well and effectively where PAI teachers provide understanding, explain, direct about good personal to students, while teachers BK control student's daily attitude outside the classroom by rebuking, saying hello, advices and giving good examples. The results showed akhlakul karimah students in the form of discipline, honest, polite, speak well, and able to control emotions. Keywords: Collaboration; Teacher; Morals; Students. Penelitian ini menggambarkan tentang profil akhlak siswa, kolaborasi guru BK dengan guru PAI, dan hasil yang dicapai dari kolaborasi tersebut dalam membentuk akhlakul karimah siswa di Madrasah Tsanawiyah Al-Mukhlisin. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Berdasarkan hasil penelitian diketahui strategi kolaboratif guru BK dengan guru PAI di Madrasah Tsanawiyah Al-Mukhlisin berjalan dengan baik dan efektif dimana guru PAI memberikan pemahaman, menjelaskan, mengarahkan tentang pribadi yang baik kepada siswa, sedangkan guru BK mengontrol sikap keseharian siswa di luar kelas dengan menegur, memberi sapaan, nasehat dan memberikan contoh. Hasil penelitian menunjukan akhlakul karimah siswa berupa disiplin, jujur, sopan, bertutur kata dengan baik, serta mampu mengontrol emosi. Kata Kunci : kolaborasi; guru; akhlak; siswa.